The Growth of Medical Knowledge
VIII, 196 p.
Keywords: The growth of knowledge and its effects on the practice of medicine have been issues of philosophical and ethical interest for several decades and will remain so for many years to come. The outline of the present volume was conceived nearly three years ago. In 1987, a conference on this theme was held in Maastricht, the Netherlands, on the occasion of the founding of the European Society for Philosophy of Medicine and Health Care (ESPMH). Most of the chapters of this book are derived from papers presented at that meeting, and for the purpose of editing the book Stuart Spicker, Ph. D. , joined two founding members of ESPMH, Henk ten Have and Gerrit Kimsma. The three of them successfully brought together a number of interesting contribu tions to the theme, and ESPMH is grateful and proud to have initiated the production of this volume. The Society intends that annual meetings be held in different European countries on a rotating basis and to publish volumes related to these meetings whenever feasible. In 1988, the second conference was held in Aarhus, Denmark on "Values in Medical Decision Making and Resource Allocation in Health Care". In 1989, a meeting was held in Czestochowa, Poland, on "European Traditions in Philosophy of Medicine. From Brentano to Bieganski". It is hoped that these conferences and the books to be derived from them, will initiate a new European tradition, lasting well into the 21 st century! P. J.